DNA Methylation Urine Biomarkers Test in the Diagnosis of Upper Tract Urothelial Carcinoma: Results from a Single-Center Prospective Clinical Trial. Issue 3 (12th September 2022) - Territo, Angelo; Gallioli, Andrea; Diana, Pietro; Boissier, Romain; Fontana, Matteo; Gaya, Josep Maria; Sanguedolce, Francesco; Calderón, Julio; Piana, Alberto; Fontanet, Sofia; Algaba, Ferran; Palou, Joan; et al.
Abstract : Purpose: The correct risk categorization and staging of upper tract urothelial cancer (UTUC) is key for disease management. Computerized tomography urography and urinary cytology have limited accuracy for risk stratification of UTUC. Ureteroscopy may increase the risk of bladder cancer recurrence. Recently, Bladder EpiCheck TM (EpiCheck) showed a high accuracy in the detection of bladder cancer. The aim of the study is to investigate the diagnostic accuracy of EpiCheck in the clinical management of UTUC and to compare it with urinary cytology. Materials and Methods: In this single-arm, blinded, prospective, single-center study (February 2019–December 2020), all patients who were candidates for ureteroscopy for suspicion of UTUC were included. Bladder and upper urinary tract (UUT) samples were collected before ureteroscopy to test for cytology and Epicheck. EpiCheck accuracy was calculated in bladder and UUT samples and compared to cytology. Results: EpiCheck resulted diagnostic in 83/86 (97%) and 73/75 (97%) of UUT and bladder samples. Histology was positive in 47/83 (57%) and 42/73 (58%) cases, respectively. In UUT samples, EpiCheck yielded a sensitivity/specificity/ negative predictive value (NPV)/positive predictive value of 83%/79%/77%/84% vs 59%/88%/61%/87% of cytology. The sensitivity/NPV for high-grade tumors was 96%/97% for EpiCheck vs 71%/86% for cytology. EpiCheck indicated ureteroscopy in 45/80 (56%) patients, missing 17%/4% of all/high-grade UTUC with 9% of unnecessary ureteroscopy. In bladder samples, the sensitivity/NPV for high-grade tumors was 71%/88% for EpiCheck and 59%/87% for cytology. Conclusions: Epicheck may be an important tool to decrease the number of unnecessary ureteroscopy. The clinical implementation of EpiCheck in UTUC warrants further investigation in multicentric prospective randomized trials.